RUMAH BELAJAR SEBAGAI UPAYA UNTUK MELINDUNGI PENDERITA TUNADAKSA - Kenly Andrianus; Himaladin Himaladin (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
Physically disabled people are people who have movement disorders due to paralysis, deformities and/or body functions, and limb abnormalities. The Jakarta city is the city with the most disabled people in Indonesia. Even so, the city of Jakarta is very minimal in providing facilities and amenities to help the lives of people with disabilities with disabilities. Building aspects related to the comfort, safety and convenience of disabled people are often forgotten in public buildings. Apart from that, social discrimination, difficulty in care, and lack of awareness of disabled people with disabilities also contribute to the low quality of life for people with disabilities. This inhospitable environment for disabled people also affects their well-being and ability to live independently. Therefore, attention to the needs of disabled people and a supportive environment for them is very important and needed. With architectural empathy, it is expected to be able to design a building that focuses on the needs of the disabled. This design will later use the Inclusive Architecture concept so that it can focus on the needs of building users. In addition to using the concept of Inclusive Architecture, the authors also use the spatial protection design method. This spatial protection method will later be applied to the circulation system and the form of this building. Keywords: architecture inclusive; emphaty architecture; physically disabled people; spatial protection Abstrak Tunadaksa adalah orang yang memiliki gangguan gerak akibat kelumpuhan, kelainan bentuk dan/atau fungsi tubuh, serta kelainan anggota gerak. Kota Jakarta merupakan kota dengan penderita tunadaksa terbanyak di Indonesia. Meskipun begitu kota Jakarta sangat minim dalam penyediaan sarana dan fasilitas untuk membantu kehidupan penyandang disabilitas tunadaksa. Aspek bangunan yang berhubungan dengan kenyamanan, keamanan dan kemudahan penderita tunadaksa, seringkali terlupakan dalam bangunan umum. Selain itu, diskriminasi sosial, sulitnya perawatan, serta kurangnya kesadaran atas penderita tunadaksa ini, juga turut menyebabkan rendahnya kualitas hidup penyandang disabilitas tunadaksa. Lingkungan yang tidak ramah bagi penyandang tunadaksa ini juga ikut mempengaruhi kesejahteraan dan kemampuan mereka untuk hidup mandiri. Oleh karena itu, perhatian terhadap kebutuhan penyandang tunadaksa dan lingkungan yang supportif bagi mereka sangat penting dan dibutuhkan. Dengan empati arsitektur, diharapkan dapat merancang sebuah bangunan yang berfokus pada kebutuhan penderita tunadaksa tersebut. Perancangan ini nantinya akan menggunakan konsep Arsitektur Inklusif agar bisa berfokus pada kebutuhan pengguna bangunannya. Selain penggunaan konsep Arsitektur Inklusif, penulis juga menggunakan metode desain proteksi spasial. Metode proteksi spasial ini nantinya akan diterapkan pada sistem sirkulas dan bentuk dari bangunan ini.